Combined effect of internal and external factors on sintering kinetics of plasma-sprayed thermal barrier coatings. Issue 5 (May 2019) - Li, Guang-Rong; Wang, Li-Shuang; Yang, Guan-Jun; Li, Cheng-Xin; Li, Chang-Jiu
Abstract: Understanding the sintering kinetics of plasma-sprayed thermal barrier coatings (PS-TBCs) is crucial to retard their performance degradation. However, under real service condition, the sintering kinetics is often affected by multiple factors. This study investigated the sintering kinetics, in a novel scale-progressive view, under the combined-effect of internal and external factors. Results show that the sintering kinetics of PS-TBCs was highly associated with their unique sintering process from nanoscale to microscale. Firstly, sintering leads to nanoscopic roughening of the pore surface. Subsequently, multiple contacts are formed between counter-surfaces. As a result, microscopic healing of pores can be finally observed. In terms of external factors, the temperature further affects the level and rate of nanoscopic roughening. This is responsible for the differences of the microscopic healing ratios, as well as the macroscopic elastic modulus.